MODL-26. CHILDREN'S BRAIN TUMOR NETWORK: ACCELERATING RESEARCH THROUGH COLLABORATION AND OPEN-SCIENCE. (4th December 2020) - Lilly, Jena; Mason, Jennifer; Appert, Elizabeth; Heath, Allison; Zhu, Yuankun; Zhang, Bo; Koptyra, Mateusz; Santi, Mariarita; Pollack, Ian; Goldman, Stewart; Leary, Sarah; Buccoliero, Anna; et al.
Abstract: The Children's Brain Tumor Network (formerly known as Children's Brain Tumor Consortium- CBTTC) is a global organization pioneering a model of open-science medical research to improve treatment and discover cures. Started in 2011, our objective was to utilize a regulatory, agreement, and governance architecture to remove existing research barriers that slowed down the pace of research and collaboration. Our network now includes 17 institutions working together to empower research. As of December 2019, over 3, 600 subjects have been enrolled resulting in collection of over 45, 000 specimens. Clinical data collection is longitudinal and includes medical history, diagnosis, treatment, pathology slides and reports, radiology imaging and reports, and outcome data. The tissue is collected flash-frozen, in freezing media, and fresh for the generation of pre-clinical models including cell lines. Blood is collected from the subject, with blood or saliva collected from the parents for germline comparison. Additionally, the Children's Brain Tumor Network- Pediatric Brain Tumor Atlas has generated 952 WGS and RNAseq, 221 proteomics, with annotated clinical data. All of this data, both generated raw and processed data, has been made available broadly to the scientific community via cloud-based platforms, including the Gabriella Miller Kids First Data Resource Portal, Cavatica, and PedCbioportal. As of January 2020, we have 45 approved biospecimen requests and 80 genomic/molecular data requests. In summary, the Children's Brain Tumor Network's goal is to accelerate the pace of discovery by providing resources and expanding the network of scientists working towards a cure.